HUBUNGAN ANTARA QUARTER LIFE CRISIS DENGAN TINGKAT SELF ESTEEM MAHASISWA DI IAKN KUPANG - Sumari Novika Manao; Marwyn Henuk; Hendrik A. E Lao (JCI Publisher, 2026)
The transition into emerging adulthood frequently induces life-direction anxiety, commonly known as a quarter-life crisis, among university students. This correlational quantitative investigation was designed to evaluate the correlation between the intensity of the quarter-life crisis (Variable X) and self-esteem (Variable Y) among active students at the State Christian Institute of Kupang (IAKN Kupang). Employing a sample of 30 participants gathered via probability sampling techniques, data collection was conducted utilizing Likert-scale questionnaires and statistically processed using the Pearson Product Moment correlation formula. The empirical analysis demonstrates a significant and highly robust positive correlation between the investigated constructs (r = 0.769; p = 0.000). This outcome highlights a noteworthy theoretical anomaly, wherein heightened levels of crisis are unexpectedly linked with enhanced self-esteem. This distinct psychological pattern is driven by active internal introspection, a purposeful pursuit of life meaning, and personal identity consolidation amid adversity. Furthermore, the campus culture at IAKN Kupang—characterized by comprehensive spiritual mentoring, robust peer networks, and a nurturing social atmosphere—serves as a constructive emotional buffer. These external dynamics empower students to navigate developmental stress adaptively, demonstrating that rather than diminishing their self-worth, the identity crisis ultimately bolsters their personal resilience.